Factors influencing the approaches to studying of preclinical and clinical students and postgraduate trainees - Wickramasinghe, Dakshitha P; Samarasekera, Dharmabandu N (Springer-Verlag, 2011)
Background Students can be classified into three categories depending on their approaches to studying; namely, deep approach (DA), strategic approach (SA) and surface apathetic or superficial approach (SAA). The aim of this study was to identify factors affecting the approaches to studying among Sri Lankan medical undergraduates and post graduate trainees and to analyze the change in the pattern of study skills with time and experience. Method Pre-clinical and clinical students of the Faculty of Medicine, University of Colombo and postgraduate trainees in Surgery at the National Hospital of Sri Lanka were invited to complete the Approaches and Study Skills Inventory for Students (ASSIST) questionnaire. Results A total of 187 pre clinical (M: F = 96:91), 124 clinical (M: F = 61:63) and 53 post graduate trainees (M: F = 50:3) participated in the study. Approaches of male and female students were similar. SA was significantly affected by age among the preclinical students (p = 0.01), but not in other groups. Among pre-clinical students, males preferred a teacher who supported understanding (p = 0.04) but females preferred a passive transmission of information (p < 0.001). This, too, was not visible among other groups. A linear regression performed on group (batch), gender, island rank at GCE Advance Level (AL) examination, self appraisal score and the preference scores of type of teacher only managed to explain 35% or less of variance observed for each approach in individual groups. Conclusion Different factors affect the approach to studying in different groups but these explain only a small fraction of the variance observed.